Eco-Enzymes Go to Schools: SMKN 5 East Kolaka's Efforts to Build Environmental Awareness and Sustainable Independence - Usman, Edi; Khatimah, Khusnul; Darajat, St. Zakiya (PT FORMOSA CENDEKIA GLOBAL, 2024)
Utilizing organic waste as a source of material to produce economically valuable and environmentally friendly products is a very positive initiative. One of the superior products that can be produced from organic waste is Eco-enzyme. This activity aims to provide students with an understanding of the process of making Eco-enzyme and its various benefits. Training and practice in making Eco-enzyme is an effective means of conveying this information to students at SMKN 5 East Kolaka. The evaluation results via questionnaires show the positive impact of this community service activity. As many as 80% of respondents stated that Eco-enzyme was in accordance with community needs, while 95% stated that their insight had increased after participating in this activity. The presence of 90% of respondents stating the benefits of this activity also reflects success in conveying information and skills to the community. In fact, the percentage of those interested in carrying out Eco-enzyme manufacturing practices increased significantly from 20% to 95%